2014
DOI: 10.14569/specialissue.2014.040303
|View full text |Cite
|
Sign up to set email alerts
|

User Satisfaction Determinants for Digital Culture Heritage Online Collections

Abstract: Abstract-The aim of this paper is to identify the possible determinants that influence user satisfaction in the context of digital cultural heritage (DCH) online collections. The data was collected in 3 stages. For the first stage, literature studies were conducted in understanding the general overview about user satisfaction in various web-domains. Next, think-aloud protocol was conducted with a group of general user with nil background of cultural heritage. Two existing digital culture heritage online collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…User satisfaction is one component of human interaction with computers. Satisfaction is defined as the act of giving what is needed or desirable [12], [13]. In every interaction between users and interfaces, achieving user satisfaction is key in determining the success of a product or system [14].…”
Section: Introductionmentioning
confidence: 99%
“…User satisfaction is one component of human interaction with computers. Satisfaction is defined as the act of giving what is needed or desirable [12], [13]. In every interaction between users and interfaces, achieving user satisfaction is key in determining the success of a product or system [14].…”
Section: Introductionmentioning
confidence: 99%
“…In any interaction between a user and an interface, achieving user satisfaction is the key in determining the success of a product or a system (Ali, Al-Refai, and Batiha, 2013); user satisfaction is subjective to measure. According to Zahidi, Lim & Woods (2014), User satisfaction results from good UX. The study of Namisango et al (2017) found that factors such as information quality, system quality, service quality, and net benefits obtained positively correlate to mobile money service use and user satisfaction.…”
Section: User Satisfactionmentioning
confidence: 99%
“…In addition, some studies have concluded that user satisfaction or fulfilment leads to quality (Ebrahimi et al, 2023;Leninkumar, 2017) while others disagree and conclude the opposite (Mishimar, 2023;Perotti et al, 2020). Concerning customer satisfaction, there are various quantification attempts and multiple definitions in modern literature (Zahidi et al, 2014). A more traditional definition (Vaezi et al, 2016) suggests that customer satisfaction has an immediate connection with the emotional judgement of the user by various encounters in educational settings.…”
Section: Introductionmentioning
confidence: 99%